Abilitation of Infants with Combined Perinatal Pathology: Capabilities of Approaches and Methods Personalization - Аlexander A. Baranov; Leyla S. Namazova-Baranova; Irina A. Belyaeva; Еlena V. Аntonova; Еlena A. Vishneva; Еlena P. Bombardirova; Vladimir I. Smirnov; Аlexsei I. Molodchenkov; Мariay О. Zubrikhina (Вопросы современной педиатрии, 2019)
Perinatal pathologies and foremost perinatal central nervous system injury are attended with delayed neurosomatic disorders frequently leading to disability. The success of realisation of individual compensation potential of every child depends on dynamics analysis of patient's condition on every survey stage, personalized choice of necessary and sufficient methods of polysystemic diseases correction. The contemporary view on ethiology and pathogenesis of main perinatal pathologies are presented in this review, main mechanisms of its development are also revealed. Recent non-invasive diagnostic technique allow to perform correction of vital signs and prevent cascade reactions of neuronal apoptosis. The sanogenetic importance of some therapeutic interventions (therapeutic hypothermia, erythropoietin, caffeine) is established in early neonatal period. The role of implementation of external factors causing epigenetic effects is clear: optimal nutrition, correction of intestinal microbiota, sensory and motional stimulation. The abilitation success depends largely on successive team activity of specialists and their collaboration with the family. Methods of multifactorial statistical analysis allow not only to prognosticate the outcomes of perinatal affection, but also to create effective mathematical models for personalized choice of facilitation measures.